2010
DOI: 10.1523/jneurosci.4967-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Prenatal Exposure to Methamphetamine and Alcohol versus Alcohol and Not Methamphetamine using Tensor-Based Brain Morphometry and Discriminant Analysis

Abstract: Here we investigate the effects of prenatal exposure to methamphetamine (MA) on local brain volume using magnetic resonance imaging. Because many who use MA during pregnancy also use alcohol, a known teratogen, we examined whether local brain volumes differed among 61 children (ages 5-15 years), 21 with prenatal MA exposure, 18 with concomitant prenatal alcohol exposure (the MAA group), 13 with heavy prenatal alcohol but not MA exposure (ALC group), and 27 unexposed controls. Volume reductions were observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
77
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(91 citation statements)
references
References 56 publications
13
77
0
1
Order By: Relevance
“…Consistent with animal-model research (Bhat et al, 2006;Dow-Edwards, 2011;Roussotte et al, 2010;Villarreal, Derrick, & Vathy, 2008;Yanai et al, 2003) and studies on functional magnetic resonance imaging (Roussotte et al, 2010;Sowell et al, 2010), children born to substanceusing women have been shown to be vulnerable across cognitive, emotional, and social functioning into adolescence.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Consistent with animal-model research (Bhat et al, 2006;Dow-Edwards, 2011;Roussotte et al, 2010;Villarreal, Derrick, & Vathy, 2008;Yanai et al, 2003) and studies on functional magnetic resonance imaging (Roussotte et al, 2010;Sowell et al, 2010), children born to substanceusing women have been shown to be vulnerable across cognitive, emotional, and social functioning into adolescence.…”
Section: Discussionmentioning
confidence: 67%
“…Promising research using neuroimaging techniques may add to the field in describing the possible teratogenic CNS effects of opiates and alcohol in the developing child. There is a growing amount of literature using neuroimaging techniques to study these effects that holds promise for understanding brain and behavior relationships (Chang et al, 2004;Sowell et al, 2010;Walhovd et al, 2007Walhovd et al, , 2010.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with rodent models, the neuroimaging literature shows prominent effects on dopamine-rich frontostriatal circuits, including volume reductions in the globus pallidus and putamen [36] and in two subregions of the caudate [38], volume increases in the anterior cingulate and inferior frontal gyrus [38], and lower diffusion in frontal white matter [39]. Metabolic abnormalities have also been reported in the striatum [40] and the frontal white matter [35].…”
Section: Introductionmentioning
confidence: 93%
“…A small sample of children with prenatal opioid exposure showed reduced global brain volume as well as regional differences including reduced volume in the cerebral cortex, amygdala, nucleus accumbens, putamen, pallidum, brainstem, cerebellar cortex, cerebellar white matter, and inferior lateral ventricles [68]. Prenatal methamphetamine exposure was linked to regional volume reductions in both striatal and limbic structures including the caudate, anterior and posterior cingulate, inferior frontal gyrus, and ventral and lateral temporal lobes; regions that are vulnerable to the neurotoxic effects of methamphetamine in adult abusers [69]. Another study showed similar results, as well as sex-specific effects of prenatal methamphetamine exposure on brain structure, including increased volume in the striatum in males and increased cortical thickness in females [70].…”
Section: Maternal and Environmental Variablesmentioning
confidence: 99%